Interoperabilidad entre plataformas blockchain con cross-chain - Caetano da Silva, Paulo (2025)
Blockchain technology requires evaluating the current state of interoperability between its platforms, to improve efficiency of the activities that are carried out and enable innovation and new services. Solutions have been proposed to facilitate interoperability between platforms, including Cross-chain technologies, which can be understood as a communication protocol. Some interoperability solutions present problems, e.g., being limited to the exchange of assets, inefficiency in complex scenarios, and introducing a centralizing element of trust that contradicts the principle of decentralization of blockchain networks. Interoperability depends on studies on decentralized consensus, Cross-chain security, and standardized mechanisms that ensure that platforms, regardless of their structural differences, can interact in a secure, efficient, and scalable manner. Therefore, a study on the state of the art related to Cross-chain, which is the most widely used technique, is necessary. So, the recommendations of Kitchenham and Charters (2007) and the quality criteria proposed by Dybå and Dingsøyr (2008) were followed. Searches were performed in the IEEE repository, identifying 1,440 articles. After refining the search and executing the methodological process, 14 articles remained. The results provide an overview of the state of the art on interoperability between blockchain platforms, indicating that this is an incipient topic in the blockchain ecosystem.